Taking the opportunity of COVID testing to screen vulnerable populations for hepatitis B, hepatitis C, syphilis, and human immunodeficiency virus in Central Brazil. - Gabriel Francisco da Silva Filho; Antoninho Barros Milhomem; Bruno Vinícius Diniz E Silva; Kamila Cardoso Dos Santos; Grazielle Rosa da Costa E Silva; Larissa Silva Magalhães; Winny Éveny Alves Moura; Thaynara Lorrane Silva Martins; Wanessa de Oliveira Gonçalves; Marcia Alves Dias Matos; Roxana Isabel Cardozo Gonzales; Leonora Rezende Pacheco; et al. (PLoS ONE)
Vulnerable populations were disproportionally affected by the coronavirus disease 2019 (COVID-19) pandemic and its peak periods disrupted progress toward the control and prevention of sexually transmitted infections (STIs). This study aimed to investigate the prevalence and factors associated with hepatitis B virus (HBV), hepatitis C virus (HCV), syphilis, and human immunodeficiency virus (HIV) among socio-economically vulnerable populations during the COVID-2019 pandemic in Goiania, Central Brazil. A total of 627 individuals, including lesbian, gay, bisexual, and transgender people, homeless individuals, waste recyclable collectors, and immigrants/refugees, were tested for these infections. Multiple Poisson regression models were used to analyze the factors associated with each outcome. HBV exposure markers were found in 16.1% of participants, antibodies against HCV (anti-HCV) in 1.9%, syphilis in 17.2%, and antibodies against HIV (anti-HIV) in 6.1%. Thirty-two individuals exhibited serological evidence of active syphilis, whereas HBV deoxyribonucleic acid and HCV ribonucleic acid were detected in six and two individuals, respectively. Increased age was statistically associated with HCV, HBV, and syphilis; identifying as LGBT and reporting a history of STIs was associated with syphilis and HIV. Illicit drug use was associated with HCV and HIV, whereas being an immigrant/refugee or engaging in transactional sex was linked to HBV. Homelessness and reporting a higher number of sexual partners in the previous month were associated with syphilis. High prevalence rates of these infections were identified, with many participants showing evidence of active infections, increasing the risk of transmission. Specific risk behaviors were associated with each infection, emphasizing the need to tailor prevention strategies to address these behaviors effectively.